2008
DOI: 10.3354/ame01243
|View full text |Cite
|
Sign up to set email alerts
|

Ciliate community in the oligotrophic Gulf of Aqaba, Red Sea

Abstract: Ciliate data were gathered along a 600 m deepwater column in central waters of the Gulf of Aqaba, Israel. Samples were taken during winter mixing, the onset of stratification in spring and during summer stratification (2003 to 2005). The phytoplankton community strongly differed in these 3 periods, from highest abundances of eukaryotic algae during mixing, followed by a Synechococcus bloom right after the onset of stratification and a Prochlorococcus-dominated community in summer. Ciliate abundance and biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Larger cells (>8 μm) are dominated by dinoflagellates and ciliates (Berninger & Wickham, 2005). The ciliates prey on the dominant picoautotrophs so that this primary production then becomes available to metazoan grazers (Claessens et al, 2008). Stable isotope analyses revealed a complex and diverse planktonic community that included herbivores and a large variety of omnivores (e.g.…”
Section: North Red Seamentioning
confidence: 99%
“…Larger cells (>8 μm) are dominated by dinoflagellates and ciliates (Berninger & Wickham, 2005). The ciliates prey on the dominant picoautotrophs so that this primary production then becomes available to metazoan grazers (Claessens et al, 2008). Stable isotope analyses revealed a complex and diverse planktonic community that included herbivores and a large variety of omnivores (e.g.…”
Section: North Red Seamentioning
confidence: 99%
“…However, despite the oligotrophic status of the Gulf of Aqaba, which was supported by very low densities of autotrophic nanoflagellates, ciliate density was unexpectedly high. This was the case not only during nutrient-replete conditions in spring, but also in summer, when nutrients were strongly depleted (Claessens et al, 2008). This suggests that the ciliate community in the Gulf of Aqaba is much more efficient in utilizing nanophytoplankton as a food source during all seasons, and that the degree of topdown control (predation) of the ciliate community is relatively low in the gulf (although alternative food sources could be heterotrophic bacteria and heterotrophic nanoflagellates).…”
Section: Discussionmentioning
confidence: 73%
“…The lower ciliate population density at Abu Galoum (site 3), for example, was still two times higher than that found at the northern part of the Gulf of Aqaba (3534 cells L -1 ) in the earlier study by Claessens et al (2008). Moreover, the densities of ciliate populations in the Gulf of Aqaba were up to eight-fold higher than abundances in other comparable studies in nutrient poor systems (Revelante and Gilmartin 1990;James and Hall, 1995;Pitta et al, 2001) and were comparable with maximum values found in coastal waters or in more productive open ocean systems (Stoecker et al, 1989;Leakey et al, 1996).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The ratio of ciliate carbon to chl a in open MW has been reported to range from 2 to 5 (Dolan & Marasé 1995, Dolan et al 1999. Claessens et al (2008) have recently reported values from 2 to 26 in the oligotrophic Red Sea. According to these authors, the higher this ratio, the higher the efficiency of ciliates in using algae as a food source.…”
Section: Ciliated Ingestion Of Pico-and Nano-algaementioning
confidence: 99%